Enhancing Digital Skills of Early Childhood Teachers Through Online Science, Technology, Engineering, Art, Math Training Programs in Estonia - Leoste, Janika; Lavicza, Zsolt; Fenyvesi, Kristof; Tuul, Maire; Õun, Tiia (Frontiers in Education, 2022)
Teacher professional development programs, including mid- and long-term Science, Technology, Engineering, Art, Math (STEAM) courses, have recently moved from in person learning at university premises to an online environment. Whether it is a temporary change in learning methods caused by the COVID-19 restrictions or whether it will become a new normal is currently under discussion in many teacher training institutions around the world. The aim of this study was to design and implement time- and money-saving synchronous online teacher training format for conducting co-design courses for early childhood teachers in the theme of STEAM integrated learning activities. Based on Tallinn University’s curriculum of in-person training courses on the same topic, with the volume of 40 contact hours, we delivered the content in two different formats: in 11-months (as it used to be in pre-COVID period) and in 4-months, adapted to participants’ needs. We used a self-assessment survey, based on DigCompEdu framework, to assess the increase of digital competences in the two formats. The long-format course had 31 participants and the short-format course had 50 participants. The assessment was based on pre- and post-test and we used structured live video presentations to let participants retrospectively describe their learning experiences. Results indicate that the participants of both courses had improved their digital competences and achieved the learning outcomes set by course content. There was no significant difference in increase of digital competences or the way the course was perceived between participants of both courses. This brings us to the cautious consideration that it is possible to achieve desired outcomes of STEAM courses even in a shorter period when conducting them online compared to the in-person courses. There is a need for further research where results from participants of in-person and online teaching courses are compared.